2016
DOI: 10.1002/brb3.493
|View full text |Cite
|
Sign up to set email alerts
|

Physical comorbidities increase the risk of psychiatric comorbidity in multiple sclerosis

Abstract: BackgroundRisk factors for psychiatric comorbidity in multiple sclerosis (MS) are poorly understood.ObjectiveWe evaluated the association between physical comorbidity and incident depression, anxiety disorder, and bipolar disorder in a MS population relative to a matched general population cohort.MethodsUsing population‐based administrative data from Alberta, Canada we identified 9624 persons with MS, and 41,194 matches. Using validated case definitions, we estimated the incidence of depression, anxiety disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 37 publications
(81 reference statements)
1
16
2
3
Order By: Relevance
“…We found the HR for incident anxiety in men decreased with an increasing followup period, although the association was significant throughout the follow-up. Another study also failed to find a significant association between diabetes and incident anxiety (defined by claimed data), which might be attributed to the five-year gap between baseline (1994) and follow-up (1999-2011) [29]. It is unclear why the positive association between diabetes and incident anxiety was observed in men only in our study.…”
Section: Discussioncontrasting
confidence: 79%
“…We found the HR for incident anxiety in men decreased with an increasing followup period, although the association was significant throughout the follow-up. Another study also failed to find a significant association between diabetes and incident anxiety (defined by claimed data), which might be attributed to the five-year gap between baseline (1994) and follow-up (1999-2011) [29]. It is unclear why the positive association between diabetes and incident anxiety was observed in men only in our study.…”
Section: Discussioncontrasting
confidence: 79%
“…Table 2 summarizes the quality assessments performed for all studies along with a qualitative synthesis of the main study strengths and weaknesses as identified by the reviewers (for the full quality assessment tables see Tables S1 and S2). Most studies ( n = 11) were from North America 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, with an additional three studies from Europe 33, 34, 35, one from Asia 36 and one from the Middle‐East 37.…”
Section: Resultsmentioning
confidence: 99%
“…The second study by Marrie et al . 29 provided only fully adjusted estimates and found no association between diabetes and incident anxiety in an administrative database over 10 years of follow‐up. However, generalizability was limited by the fact that participants were sampled based on a diagnosis of multiple sclerosis or being a matched‐control for multiple sclerosis participants.…”
Section: Resultsmentioning
confidence: 99%
“…The average life expectancy of an MS patient has been shown to be 7-14 years less than the average person, however this reduction in life expectancy differs across MS populations 20. Several factors contribute to MS life expectancy including; early age of MS onset, sex, MS comorbidities, life style, accidents and suicide 20,21. As a complex disorder, management regimens should implement proactive life style modifications…”
mentioning
confidence: 99%